Intercalation effect on hyperfine parameters of Fe in FeSe superconductor with Tc = 42 K - Shylin, Sergii I.; Ksenofontov, Vadim; Sedlmaier, Stefan J.; Clarke, Simon J.; Cassidy, Simon J.; Wortmann, Gerhard; Medvedev, Sergey A.; Felser, Claudia (EPL - Europhysics Letters, 2015)
57Fe-Mössbauer spectra of superconducting β-FeSe, the Li/NH3 intercalate product and a subsequent sample of this intercalate treated with moist He gas have been measured in the temperature range 4.7-290 K. A correlation is established between hyperfine parameters and critical temperature in these phases. A strong increase of the isomer shift upon intercalation is explained by a charge transfer from the Li/NH3 intercalate to the FeSe layers resulting in an increase of up to 42 K. A significant decrease of the quadrupole splitting above 240 K has been attributed to diffusive motion of Li+ ions within the interlamellar space.
CRIS-Team Scopus Importer:2023-03-20